Crowdsourcing-based geoinformation, disadvantaged urbanisation challenges, sub-Saharan Africa: Theoretical perspectives and notes - Ingwe, Richard (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2017)
Scholars and practitioners concerned with geoinformation, cyber-cartography, development studies, and other subjects increasingly explore crowdsourcing and its huge advantages for development. Some have advocated it for adoption/promotion by government as a means of citizen engagement. The objective of this article is to increase the appreciation of the contribution that crowdsourcing can make towards resolving challenges associated with disadvantaged urbanisation in sub-Saharan Africa (SSA). We review urban challenges of SSA and three practices of crowdsourcing: volunteered geographic information (VGI), Citizen Science (CS), and Participatory Mapping (PM). Then we examine problems associated with the advocacy for government adoption of those practices in SSA. We argue that civil society collaboration with an international governmental organisation (IGO) instead of government promises a better way of adopting and promoting them. This suggestion is based on the fact that work related to this strategy is carried out by a global coalition of civil society, the UN-NGLS. This strategy promises a more rapid way of taking advantage of fast-tracking public engagement in the economic region, SSA.
Keywords: SSA; crowdsourcing; volunteered geographic information; Citizen Science; Participatory Mapping; civil society; IGO; UN-NGLS